Web-Based Contract Employee Payroll Information System at PT.Bridgestone Kalimantan Plantation - Asti Yana; Rahmat Hidayat; Rafie Rafie (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2025)
The payroll system for contract employees used by PT. Bridgestone Kalimantan Plantation has been relying on Microsoft Excel to calculate contract employee salaries. However, using Microsoft Excel has several drawbacks when it comes to payroll processing, one of which is its inefficiency when dealing with large datasets. This study aims to analyze and design a web-based payroll system for contract employees to assist and simplify the process of calculating payroll for contract employees at PT. Bridgestone Kalimantan Plantation. The methods used in this study include system requirements analysis, database design, and the implementation of a web-based system using Laragon as the database. This research was conducted by analyzing the current system, obtaining data from direct interviews with parties involved in the employee payroll system, and conducting observations. The results of this research simplify the processing of contract employee data, minimize data errors, accelerate data verification and validation, and make salary calculations easier, thereby generating more effective and efficient information.